The concept of fixed-dose combination drugs in primary and secondary prevention of cardiovascular disease. Position paper of the Russian Society of Cardiology, the Russian Society for the Prevention of Noncommunicable Diseases, the Russian Scientific Medical Society of Internal Medicine, the Russian Association of Endocrinologists, the Association of Clinical Pharmacologists, the Eurasian Association of Internal Medicine, the Russian Association of Gerontologists and Geriatricians - G. P. Arutyunov; O. M. Drapkina; Zh. D. Kobalava; A. O. Konradi; Yu. M. Lopatin; S. V. Nedogoda; D. A. Sychev; O. N. Tkacheva; M. V. Shestakova; E. V. Shlyakhto; S. L. Bolotova; S. V. Villevalde; et al. (Российский кардиологический журнал, 2024)
The paper describes the position of of the Russian Society of Cardiology, the Russian Society for the Prevention of Noncommunicable Diseases, the Russian Scientific Medical Society of Internal Medicine, the Russian Association of Endocrinologists, the Association of Clinical Pharmacologists, the Eurasian Association of Internal Medicine, the Russian Association of Gerontologists and Geriatricians on the most important and controversial issues of the use of fixed-dose combination drugs in the primary and secondary prevention of cardiovascular disease.